Sports Education as a Means of Building Student Character: Values and Benefits - Maksimus Bisa (AL-ISHLAH: Jurnal Pendidikan, 2023)
Sports education offers a unique opportunity for character-building in students. The benefits of sports education go beyond just physical health. It has been found to play an important role in building character and teaching values essential for success in life. Grounded on this belief, this study examines the values that sports education can teach and their potential benefits. A qualitative research approach was employed using interviews and observations of students participating in sports education programs. The data obtained from the field were analyzed thematically. From the analysis, it is indicated that sports education can teach important values such as teamwork, leadership, determination, and sportsmanship. Additionally, sports education can benefit students, such as improved physical fitness, self-confidence, and social skills. Overall, this study suggests that sports education can play a significant role in character development and has the potential to impact students both on and off the field positively.